The Effectiviness of Student Teams Achievement Division and Scrambel Combined Model on Collaborative Skills and Conceptual Knowledge Mastery of Class X SMAN 1 Semparuk on Bacteria - Rivaldo Alphrazy; Bernadetta Octavia (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze whether or not there is a significant difference in collaboration skills and mastery of conceptual knowledge of students who follow the STADBEL combined model learning in the experimental class with students who follow the Make a Match model learning in the control class on the subject of bacteria class X SMAN 1 Semparuk. In this study used non-equivalent control group design. The research sample was students of class X MIPA SMA. Sampling used cluster random sampling technique. The instruments used consisted of conceptual knowledge mastery tests and non-test collaboration skills in the form of questionnaires and self-assessment questionnaires of student responses to learning and student responses to learning models. Learning with the STADBEL combined model can be effective on collaboration skills and mastery of conceptual knowledge of students. A Sig value of 0.027 < 0.05, it is concluded that there is a significant effect of the STADBEL combined model on collaboration skills and mastery of conceptual knowledge of students. These results indicate that the STADBEL combined model effectively improves collaboration skills and mastery of conceptual knowledge of students of SMAN 1 Semparuk class X IPA on the subject of bacteria.